THE INFLUENCE OF PRINCIPAL LEADERSHIP AND WORK MOTIVATION ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS A MEDIATING VARIABLE - Andriani Sariwardani; Hairinisa; Umalihayati (Cakrawala Pedagogik, 2025)
This study aims to analyze the influence of principal leadership and work motivation on teacher performance with job satisfaction as a mediating variable. The study was conducted with a quantitative approach using a survey method. The population studied were elementary school teachers in cluster 2 of Ciruas District, Serang Regency, totaling 5 schools in Ciruas District. The research sample consisted of 31 teachers from several elementary schools in cluster 2 of Ciruas District, Serang Regency. Data were collected through a Likert scale questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that principal leadership and work motivation had a significant effect on teacher performance, and job satisfaction significantly influenced teacher performance. In addition, job satisfaction was proven to be a mediating variable in the relationship between principal leadership and work motivation on teacher performance.